2022
DOI: 10.1001/jamaophthalmol.2022.3375
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Generative Adversarial Networks for High-Resolution Synthetic Image Generation of Circumpapillary Optical Coherence Tomography Images for Glaucoma

Abstract: IMPORTANCE Deep learning (DL) networks require large data sets for training, which can be challenging to collect clinically. Generative models could be used to generate large numbers of synthetic optical coherence tomography (OCT) images to train such DL networks for glaucoma detection.OBJECTIVE To assess whether generative models can synthesize circumpapillary optic nerve head OCT images of normal and glaucomatous eyes and determine the usability of synthetic images for training DL models for glaucoma detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The results showed that synthetic OCT images were indistinguishable from real ones to experienced clinicians. Training a DL model for glaucoma detection with synthetic images yielded comparable performance to models trained on real data and outperformed on an external data set [41]. Furthermore, this highlights the potential for privacy-agnostic data sharing.…”
Section: Synthetic Data In Glaucoma Artificial Intelligence Researchmentioning
confidence: 68%
“…The results showed that synthetic OCT images were indistinguishable from real ones to experienced clinicians. Training a DL model for glaucoma detection with synthetic images yielded comparable performance to models trained on real data and outperformed on an external data set [41]. Furthermore, this highlights the potential for privacy-agnostic data sharing.…”
Section: Synthetic Data In Glaucoma Artificial Intelligence Researchmentioning
confidence: 68%
“…In 2022 Kumar et al used GANs to create synthetic OCT circumpapillary images, evaluate them for gradeability and authenticity, and use them to train DL models [62]. The researchers created two models to generate both healthy and glaucomatous synthetic OCT images of the circumpapillary ONH.…”
Section: Using Deep Learning For Optical Coherence Tomography Angiogr...mentioning
confidence: 99%
“…These methods are standard procedures in image preprocessing, 4 but the training data sets for AI models also require expansion. Data synthesis is a new type of data augmentation, and GANs have shown potential to generate high‐quality OCT images with applications in the detection of various retinal diseases 34 and glaucoma 73 . Effective network designs such as parallel network structures, 74 cascaded network structures, 75 and FSL 14 could be beneficial in retinal OCT image analysis.…”
Section: Future Directionsmentioning
confidence: 99%